2005
DOI: 10.1021/ol051804s
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for β-Selenoglycoside Synthesis Using β-p-Methylbenzoyl Selenoglycoside as the Selenating Unit

Abstract: [reaction: see text] The reaction between alpha-glycosyl bromides and potassium p-methylselenobenzoate yields beta-p-methylbenzoyl selenoglycosides. The acyl selenoglycosides were activated by the action of a secondary amine and Cs2CO3 to produce an anomeric selenolate anion, which reacted in situ with various electrophiles to yield novel selenoglycosides while retaining the anomeric stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 13 publications
1
31
0
2
Order By: Relevance
“…Drugs bis(4-Methylbenzoyl) diselenide (Figure 1) was prepared and characterized as previously described (Kawai et al, 2005). The 1 H NMR and 13 C NMR spectra were in full agreement with its assigned structure.…”
Section: Methodsmentioning
confidence: 67%
“…Drugs bis(4-Methylbenzoyl) diselenide (Figure 1) was prepared and characterized as previously described (Kawai et al, 2005). The 1 H NMR and 13 C NMR spectra were in full agreement with its assigned structure.…”
Section: Methodsmentioning
confidence: 67%
“…[15][16][17][18] And we previously reported that selenazole derivatives can inhibit the mushroom tyrosinase. 19) Selenoglycoside (SG) series have been recently developed as a series of selenium-containing carbohydrates 20) (Fig. 1).…”
mentioning
confidence: 99%
“…A disaccharide glycosyl acceptor (7) was stereoselectively condensed with a trisaccharide glycosyl donor (12). The disaccharide derivative (7) and the trisaccharide derivative (12) were prepared from suitably protected monosaccharide intermediates 2 [12], 3 [13], 4 [14], 5 [15] and 6 [16] prepared from the commercially available reducing sugars using reported literature (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%